Simulation of shear and bending cracking in RC beam: material model and its application to impact - Mokhatar, S. N.; Sonoda, Y.; Zuki, S. S. M.; Kamarudin, A. F. (2017)
This paper presents a simple and reliable non-linear numerical analysis incorporated with fully Lagrangian method namely Smoothed Particle Hydrodynamics (SPH) to predict the impact response of the reinforced concrete (RC) beam under impact loading. The analysis includes the simulation of the effects of high mass low-velocity impact load falling on beam structures. Three basic ideas to present the localized failure of structural elements are: (1) the accurate strength of concrete and steel reinforcement during the short period (dynamic), Dynamic Increase Factor (DIF) has been employed for the effect of strain rate on the compression and tensile strength (2) linear pressure-sensitive yield criteria (Drucker-Prager type) with a new volume dependent Plane-Cap (PC) hardening in the pre-peak regime is assumed for the concrete, meanwhile, shear-strain energy criterion (Von-Mises) is applied to steel reinforcement (3) two kinds of constitutive equation are introduced to simulate the crushing and bending cracking of the beam elements. Then, these numerical analysis results were compared with the experimental test results.